2013
DOI: 10.1002/cbin.10107
|View full text |Cite
|
Sign up to set email alerts
|

RNAi‐mediated MMP‐9 silencing inhibits mouse melanoma cell invasion and migration in vitro and in vivo

Abstract: MMP-9 participates in tumour growth, invasion, metastasis and vascularisation. Thus, inhibition of MMP-9 may be involved in the process of tumourigenesis. We have investigated the effect of RNAi-mediated MMP-9 silencing on inhibiting invasion and migration of mouse melanoma cell B16. A specific and optimised siRNA vector was used to target MMP-9 mRNA synthesis in B16 cells. Changes of invasion and migration capability of B16 cell were examined after transfection at different time, and a footpad tumour model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014). Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014). Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is one of the most important metalloproteases and is critical in regulating ECM dissolution, activating growth factors as well as initiating intracellular signaling leading to tumor progression and metastasis (26)(27)(28)(29). Several studies have demonstrated that inhibiting the activities of MMP-9 by RNAi resulted in apoptosis in melanoma cells (15), malignant meningioma cells (27) and medulloblastoma cells (28). Knocking down the expression of MMP-9 significantly inhibited MMP-9 levels and altered downstream signaling molecules, thereby leading to transcriptional inhibition of anti-apoptotic molecules and directing the cells towards apoptosis (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that MMP-9 stimulates tumor cell growth, migration, invasion and metastasis and regulates tumor angiogenesis by releasing vascular endothelial growth factor (VEGF)-A from an extracellular reservoir (12)(13)(14). A previous study demonstrated that downregulation of MMP-9 by RNA interference (RNAi) inhibited cancer cell invasion and metastasis (15). Taken together, these studies suggest that MMP-9 is important in tumorigenesis and metastasis.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, siRNA specific to the TPX2 gene was transfected into EO9706 by liposome transfection method and the gene suppression was confirmed. Studies have shown that siRNA transfection can demonstrate the interference effect in 6 h, and can last for 72 h or longer [23,24]. To observe and compare the changes of cell biological characteristics after interference majority of experiments were performed for 48 h or 72 h. [25] In our experiment, RT-PCR and Western-blot results both showed that 42-72 h after siRNA targeted at TPX2 in EC9706 cell was transfected, expected results for gene knock-down came on the scene.…”
Section: Discussionmentioning
confidence: 99%